A Study on metaphors in “The Catcher in the Rye” by J.D. Salinger via its Vietnamese version translated by Phùng Khánh = Nghiên cứu về ẩn dụ trong tác phẩm “Bắt trẻ đồng xanh” của J.D. Salinger qua bản dịch tiếng Việt của dịch giả Phùng Khánh - Vương, Thị Thanh Nhàn (2020)
Metaphor has been considered to be one of most important rhetorical devices which contributes to the success of literary works. It embellishes the beauty of language and convey meaningful underlying messages to the readers. However, linguistic and cultural differences, translation of metaphor is a real challenge, which brings difficulties and even loss in meaning. The study focused on English-Vietnamese translation through the English novel of “The Catcher in the Rye” written by J.D. Salinger and its Vietnamese version “Bắt trẻ đồng xanh” translated by Phùng Khánh. This research aimed to help students of translation and interpretation division of ULIS-VNU, new translators or readers have certain understanding about metaphor and metaphor translation. The study achieved this purpose when a comparative analysis of 73 English metaphors and translation strategies applied by Phung Khanh indicated that metaphors were categorized into 6 types and translated by 7 strategies applied by Phùng Khánh according to Newmark’s framework. Loss of meaning in translated metaphor compared to original ones were also thoroughly analyzed. The results showed that original metaphor was the most preferred by the author. Among 7 strategies applied, reproducing the same image in the TL and converting a metaphor to its sense are more frequently used by the translator, which helped the translation smooth and natural than the others. Most metaphors are translated accurately; however, there was still loss of meaning in some equivalences, mostly on connotative meaning